1999
DOI: 10.1111/j.1572-0241.1999.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Visceral Perception in Patients With Pain-Predominant Irritable Bowel Syndrome

Abstract: In a tertiary referral population of IBS patients: 1) abdominal pain is reported by only one third of patients as their most bothersome viscerosensory symptoms; and 2) pain-predominance correlates with development of rectal hypersensitivity after a noxious sigmoid stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(85 citation statements)
references
References 25 publications
2
81
1
1
Order By: Relevance
“…13 Furthermore, it was also shown previously that patients with pain predominant IBS were more susceptible to rectal sensitization in response to repetitive sigmoid distension, compared with non-pain predominant IBS patients. 22 These findings suggest that there may be an association between pain and visceral hypersensitivity. To evaluate the possible predictive value of this symptom, we performed an A-ROC curve analysis.…”
Section: Discussionmentioning
confidence: 73%
“…13 Furthermore, it was also shown previously that patients with pain predominant IBS were more susceptible to rectal sensitization in response to repetitive sigmoid distension, compared with non-pain predominant IBS patients. 22 These findings suggest that there may be an association between pain and visceral hypersensitivity. To evaluate the possible predictive value of this symptom, we performed an A-ROC curve analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, it has been suggested that visceral hyperalgesia, the phenomenon whereby stimuli normally not experienced as painful become so, is highly specific for IBS [21] . Visceral hypersensitivity, visceral hyperalgesia and viscero-somatic referral (the phenomenon whereby stimuli are referred over wide areas) have, indeed, been confirmed, in IBS, in more recent studies, using a variety of methodologies and under controlled experimental conditions [22] . While visceral hyperalgesia has been postulated as being highly specific for IBS, it alone or in association with other manifestations of hypersensitivity cannot explain all of IBS; even the most celebrated enthusiasts for the sensory hypothesis concede that sensation is normal in some patients.…”
Section: Visceral Hypersensitivity and Hyperalgesiamentioning
confidence: 97%
“…Recognition of this fact is important from a therapeutic point of view, as successful management is dependent on targeting the features that the patient finds most troublesome. It is becoming increasingly recognized that abdominal distension is very distressing for many patients (3), but the pathophysiology of this symptom is poorly understood, although the obvious explanation of excessive gas is unlikely to be the whole answer (4,5). Thus, although patients often attribute bloating to gas, this is not always the case.…”
Section: The Problem Of Gas In Irritable Bowel Syndromementioning
confidence: 83%
“…Patients with irritable bowel syndrome (IBS) complain of a constellation of symptoms (1), of which abdominal pain is not necessarily the most intrusive (2,3). Recognition of this fact is important from a therapeutic point of view, as successful management is dependent on targeting the features that the patient finds most troublesome.…”
Section: The Problem Of Gas In Irritable Bowel Syndromementioning
confidence: 99%